Auditory filtering at low frequencies - SĘK, A. P. (Archives of Acoustics, 2000)
This paper is concerned with the comparison of the critical bandwidth (CB) and the equivalent rectangular bandwidth (ERB) of the auditory filters at low frequencies. The method of critical bandwidth determination based on the critical modulation frequency (CMF) has been questioned, particularly for frequencies less than 500 Hz. The CMF, which is the modulation frequency at which amplitude modulation (AM) and frequency modulation (FM) detection thresholds become identical, is confounded as a proper measure of the auditory filter's width. It refers to the modulation rate for which one of the sidebands is most detectable. For low carrier frequencies the higher sideband is most detectable whereas for higher carrier frequencies the lower sideband becomes most detectable. Thus, at least for low carrier frequencies (i.e. less than 200 Hz), the CMF does not reflect the auditory system's sensitivity for detecting the phase differences of the spectral components of the signal. These findings can account for the fact that the critical bandwidth flattens off at low carrier frequencies, whereas the equivalent rectangular bandwidth of the auditory filters continues to decrease down to very low centre frequencies. It was also shown that, at least for very low frequencies, critical bands do not reflect directly the auditory filtering that takes place in the peripheral auditory system.